Konsep Pendidikan Islam Perspektif HOS Tjokroaminoto - Alfian Nur Mustofa Kamil (STAI Terpadu Yogyakarta, 2018)
This research is motivated by the fact that there are still many young people who still do not know the thought of HOS Tjokroaminoto in the field of Islamic education. Most people think that HOS Cokroaminoto is better known as a great agitator and politician, has no concept of Islamic education. Even more concerning again the young generation is now especially junior high school students who do not know the names of national heroes of Indonesia's movement. Meanwhile, some people also tend to think that HOS Cokroaminoto is only a political party figure, when he is a national hero who has been instrumental in laying the foundations on various national issues. But until now his capacity as an extraordinary figure is lacking the national spotlight. The younger generation recognizes the street name of HOS Cokroaminoto, the school name of Cokroaminoto but does not understand who exactly is HOS Cokroaminoto and how the footsteps of his struggle. From this research can be described that education and teaching desired by HOS Tjokroaminoto is, to form a true and virtuous and democratic Muslim man, competent and responsible for the welfare of Nusa and Bangsanya, so it becomes a source of mercy for the whole of nature. And in azaz program and tandhim program of Syarikat Islam mentioned that the matter of education should not be the nature and the despair of humankind. Education initiated by HOS Tjokroaminoto also should not separate general science and religion. This is conceived by the intention to form an academic and religious human who has the spirit of Islam, freespirited and democratic and broad-minded and insightful love of the homeland. The principle of education is the feeling of nationalism of nationalism must remain preferred in terms of studying various types of knowledge. Not to happen after studying the various sciences, we are more west of the westerners themselves or more than the Arabs themselves.